A low-carbon evaluation method for manufacturing products based on fuzzy mathematics. Issue 1 (1st January 2020) - Dong, Chaoqun; Bi, Kexin
Abstract: According to the functional structure and design structure of the manufacturing products, a low-carbon evaluation index system is established for product maintenance and support system, where the particularity of the working environment of manufacturing products, the maintenance ability and the support tasks of equipment manufacturing products are all considered. In particular, the expert evaluation method and the empirical analysis of factory technologists are used for a single index, and a recursive algorithm is given. According to the principle of the maximum membership degree, the merits and demerits based on the membership degree of the comments are evaluated, and both the multi-level index system and the fuzzy comprehensive evaluation method are combined. In addition, a comprehensive evaluation method, i.e. Multi-level Fuzzy Correlation Clustering Analysis (MFCCA) with a clear idea, is given for the low-carbon evaluation of the manufacturing products. Finally, the correctness, effectiveness and superiority of the proposed method are verified via the test experiments of an electric machine factory in the manufacturing industry.